Commander in cheat : how golf explains Trump - Reilly, Rick (Hachette Books, 2019)
Donald Trump loves golf. He loves to play it, buy it, build it, and operate it. He owns 14 courses around the world and runs another five, all of which he insists are the best on the planet. He also claims he's a 3 handicap, almost never loses, and has won an astonishing 18 club championships. How much of all that is true? Almost none of it, acclaimed sportswriter Rick Reilly reveals in this unsparing look at Trump in the world of golf. Based on Reilly's own experiences with Trump as well as interviews with over 100 golf pros, amateurs, developers, and caddies, Commander in Cheat is a startling and at times hilarious indictment of Trump and his golf game. You'll learn how Trump cheats (sometimes with the help of his caddies and Secret Service agents), lies about his scores (the "Trump Bump"), tells whoppers about the rank of his courses and their worth (declaring that every one of them is worth $50 million), and tramples the etiquette of the game (driving on greens doesn't help). Trump doesn't brag so much, though, about the golf contractors he stiffs, the course neighbors he intimidates, or the way his golf decisions wind up infecting his political ones.